Development of a Remote Monitoring System for Voltage Measurements in Cathodic Protection - Omar, Muhammad Zahir Asyraf; Mohamad, Khairul Anuar (Evolution in Electrical and Electronic Engineering, 2023)
Underground pipelines are one of the most important infrastructures in the world for transporting liquid or gas, such as natural gas, biofuels, and liquid petroleum. One major challenge in pipeline operation is a corrosion attack that significantly contributes to high-cost maintenance. Therefore, the monitoring system needs to be improved to provide an early warning to the operators or cathodic protection (CP) technicians for immediate mitigation planning and simultaneously speed up the maintenance work. The developed device is equipped with an integrated op-amp circuit as the voltage sensor and NEO-6M GPS Module as the positioning location. In addition, Blynk is used as an analytics platform to develop an interface to monitor voltage parameters. The findings indicate that the device could measure voltage readings as precisely as a multimeter with an accuracy of 98.8% maximum to 96.2% minimum. Based on the data collection, the voltage output of the op-amp circuit is reliable and can also measure the voltage reading of a corroded steel pipeline in a scale model of a cathodic protection system. Thus, the developed system enables remote monitoring and acknowledges the parameter in the cathodic protection system anywhere and anytime without frequent site visits.